Differential housing inclusion for newly arrived refugees in a Swedish context - Eva Wikström; Madeleine Eriksson (Tidsskrift for boligforskning)
In depictions of the Swedish welfare regime, there is a belief concerning the existence of a strong link between the universalism of rights and residency. But with tougher migration laws, temporary and time-limited residence permits, the settlement of different groups and access to housing and other social rights have been made more difficult. Public housing is often used as a means of providing housing for refugees, where time-limited subletting contracts are frequently used, writing off tenants’ rights to possession. While there is a strong tradition of universal public rental housing without means testing in the Swedish housing supply, the institutional practices of housing provision for refugees deviate from universal features. In this paper, we examine the outcome of housing provision for refugees in one municipal setting. Our study is based on qualitative interviews with 19 officials and politicians about arguments and justifications concerning the housing practices in use. The analysis also includes interviews with 11 refugees with varying immigration status, focusing on their experiences of housing solutions and tenant rights. Our results show that the municipal responsibility to provide housing for refugees reciprocates immigration control, which produces not only variation in fulfilment of decent housing, but also differential inclusion based on a locally practised categorization of housing rights.